Change in prevalence rates of physical and sexual intimate partner violence against women: data from two cross-sectional studies in New Zealand, 2003 and 2019. Issue 3 (23rd March 2021) - Fanslow, Janet; Hashemi, Ladan; Malihi, Zarintaj; Gulliver, Pauline; McIntosh, Tracey
Abstract : Objectives: To explore changes in reported prevalence of physical and sexual intimate partner violence (IPV) between 2003 and 2019. The impact of sociodemographic differences between the two samples and between group differences were also examined. Changes in attitudes supportive of violence and in help-seeking behaviour following disclosure were also explored. Design: Two cross-sectional studies. Setting and participants: Cross-sectional studies on family violence conducted in New Zealand in 2003 and 2019. Ever-partnered female respondents aged 18–64 years old were included (2003 n=2674, 2019 n=944). Main outcome measures: Prevalence rates of lifetime and past 12-month physical and sexual IPV, attitudes towards gender roles and acceptability of a man hitting his wife, help sought and received following disclosure were compared between the study years. Results: Lifetime prevalence of physical IPV was unchanged between 2003 and 2019 (AOR=0.89; 95% CI 0.73 to 1.08). There was a significant decrease in the proportion of women who reported experiencing 12-month physical IPV (AOR=0.53; 95% CI 0.29 to 0.97). Small reductions in rates for lifetime sexual IPV were also observed (AOR=0.74; 95% CI 0.59 to 0.95). In 2019, fewer women agreed with one or more statements supportive of traditional gender roles (48.1% (95% CI 45.7% to 50.5%) in 2003; 38.4% (95% CI 33.8% to 43.2%) in 2019). A significant decrease was noted in the proportion of women who sought help from informal sources (from 71.3% (95% CI 68.1% to 74.2%) in 2003 to 64.6% (95% CI 58.7% to 70.1%) in 2019). No significant changes in seeking help from formal sources, or perceived helpfulness from any source were noted. Conclusion: While the reductions in 12-month physical and lifetime sexual IPV are positive, prevention efforts need to be established, maintained and strengthened to address the substantial lifetime prevalence of IPV. Efforts to strengthen responses from formal and informal sources continue to be needed.